Evaluation of Dentists' Knowledge in a Brazilian city about Managing Dental Injuries in Children According to IADT Guidelines: A Cross-Sectional Study - Felipe de Souza Matos; Maria Cecília Pereira Marinho; Caio Luiz Lins-Candeiro; João Marcos da Costa Ribeiro; Walbert de Andrade Vieira; Luiz Renato Paranhos (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To evaluate the knowledge level of dentists in Mossoró, RN, Brazil, regarding dental trauma management based on the current guidelines of the International Association of Dental Traumatology (IADT). Material and Methods: Dentists working in Mossoró and regularly registered with the Regional Dentistry Council of Rio Grande do Norte responded to a printed or digital questionnaire investigating sociodemographic and professional profiles with 12 questions about dental trauma management. Jamovi 2.3.28.0 software assisted the statistical comparisons between subcategories relating to the participants' sociodemographic and professional profiles, with a 5% significance level. Results:69 dentists participated in the study. The mean percentage of correct answers was 50.24%, including all inquiries. The lowest rates of correct answers regarded tooth intrusion and avulsion (14.5% and 31.88%, respectively). The overall median score for the proper management of dental trauma was 6.0 points, considering a maximum possible score of 12, categorizing the participants' overall knowledge as acceptable. Sex, clinical experience, postgraduate degree, primary activity sector, the number of previously treated cases, and self-reported knowledge of dental trauma did not significantly affect dentists' knowledge level. Conclusion: The knowledge level of dentists in Mossoró regarding dental trauma management is acceptable based on current IADT guidelines.